Cooperative optimal power flow with flexible chemical process loads. Issue 4 (1st February 2021) - Otashu, Joannah I.; Seo, Kyeongjun; Baldea, Michael
Abstract: Power systems operations involve dispatching generation capacity and ancillary services as required to sustain reliable functioning of the electric grid. The dispatch schedules are determined by solving power flow calculations that incorporate models of the network components in real time as the power grid conditions change. Electricity intensive chemical processes can potentially provide grid support services and a closer coordination between process and grid operations can be beneficial. This cooperation is hindered by the lack of suitable process models, which appropriately protect process information. We propose a means to model the grid‐relevant dynamics of chemical processes, and a framework for embedding such models in optimal power flow calculations. We present an extensive case study concerning cooperative demand‐response operation for an electricity‐intensive chemical process, chlor‐alkali production. The results indicate significant flexibility and economic benefits both at the utility and at the end‐user levels.